Are the prevalence and treatment of asthma similar in elite athletes and the aged-matched non-athlete population? - Locke, S.; Marks, G. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The objective of this study was to determine the prevalence of asthma and use of asthma medications in elite athletes compared with an age-matched non-athlete population. Data were collected from the respiratory component of annual medical screening of 424 elite athletes from the Queensland Academy of Sport. Measures included the prevalence of current asthma and ever doctor-diagnosed asthma, and the prevalence of use of treatment for asthma including ß-agonists and inhaled corticosteroid medication. The prevalence of current asthma in athletes aged 18-29 years was 14% (95% CI, 9-19%), which did not differ significantly from the prevalence in the non-athlete control population (11%; 95% CI, 9-12%, P=0.3). Of athletes with current asthma, 27% were not taking any medications for asthma, and 25% were treated with short-acting ß-agonist medications alone and were not taking inhaled corticosteroids. These data indicate that the overall cumulative and period prevalence of asthma in Queensland athletes is similar to that in the general age-matched population. Athletes use ß-agonists with a frequency similar to the general population.